2021
DOI: 10.1111/jph.13002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Venturia pyrina virulence on European pear (Pyrus communis) cultivars by an in vitro methodology

Abstract: If fungicides are not applied, in weather conditions conducive to the disease and on susceptible cultivars, yield loss can reach 40%-100% (Shabi, 1990;Sokolova et al., 2014).In several regions, the pear scab is effectively controlled by the regular use of fungicides and the cultivation of resistant or tolerant varieties, such as 'Conference', 'Abbé Fètel' and 'Navara'

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
(137 reference statements)
1
1
0
Order By: Relevance
“…Notably, quite a large proportion of interactions considered incompatible were scored as 3a (moderately resistant), whereas most interactions considered compatible were Screening of Venturia inaequalis virulence and resistance of Malus genotypes to apple scab using in vitro methodology Olga Sokolova, Inga Moročko-Bičevska noted as partially susceptible (score 3b). The two types of interactions with scores 3b (partially susceptible, considered as compatible) and 3a (partially resistant) were possible to differentiate with confidence only when the evaluation was supplemented with microscopic examination, as noted before in similar studies (Pierantoni et al, 2007;Sokolova & Moročko-Bičevska, 2021). Similarly, as in other studies (Caffier et al, 2015), susceptible phenotype (score 4 reflected as "+") was rarely observed and often was not consistent among the tests.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Notably, quite a large proportion of interactions considered incompatible were scored as 3a (moderately resistant), whereas most interactions considered compatible were Screening of Venturia inaequalis virulence and resistance of Malus genotypes to apple scab using in vitro methodology Olga Sokolova, Inga Moročko-Bičevska noted as partially susceptible (score 3b). The two types of interactions with scores 3b (partially susceptible, considered as compatible) and 3a (partially resistant) were possible to differentiate with confidence only when the evaluation was supplemented with microscopic examination, as noted before in similar studies (Pierantoni et al, 2007;Sokolova & Moročko-Bičevska, 2021). Similarly, as in other studies (Caffier et al, 2015), susceptible phenotype (score 4 reflected as "+") was rarely observed and often was not consistent among the tests.…”
Section: Discussionsupporting
confidence: 61%
“…increasing or decreasing the concentration of spores in some sites and causing changes in tissue reaction (Caffier et al, 2015;Pétriacq, Stassen, & Ton, 2016). Similarly, as in experiments with pear detached fruits and leaves (Sokolova & Moročko-Bičevska, 2021), maintenance of leaves for more than two to three weeks was not possible that was needed to develop typical scab lesions with abundant pathogen sporulation. Such problems were not observed in tests with fruits.…”
Section: Discussionmentioning
confidence: 99%